2016
DOI: 10.1016/j.appdev.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of parents' and teachers' beliefs in children's self-concept development

Abstract: This study examined to what extent parents' and teachers' beliefs about children's abilities predict children's self-concept of math and reading ability development during the first grade, and whether these predictions depend on the child's gender and level of performance. One hundred fifty-two children and their parents and teachers were followed across first grade. The results showed, first, that the associations between teachers' beliefs and children's subsequent self-concept of ability depended on the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 46 publications
(96 reference statements)
3
32
0
2
Order By: Relevance
“…However, the differential role that parental beliefs have on student self-concept, depending on the student's level of performance, has not to our knowledge been investigated among older children like secondary school students. Finding out differences in the associations between parental beliefs and students' self-concept of ability depending on students' level of performance might have important implications for interventions.One further limitation of earlier research is that the majority of studies on the role of parental beliefs have focused on the role of mothers (for exceptions, see Frome & Eccles, 1998;Pesu et al, 2016), to the relative neglect of the role of fathers' beliefs. However, it might be that mothers and fathers play a different role in their children's self-concept development (Frome & Eccles, 1998; MacGrath & Repetti, 2000;Maccoby, 1998).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…However, the differential role that parental beliefs have on student self-concept, depending on the student's level of performance, has not to our knowledge been investigated among older children like secondary school students. Finding out differences in the associations between parental beliefs and students' self-concept of ability depending on students' level of performance might have important implications for interventions.One further limitation of earlier research is that the majority of studies on the role of parental beliefs have focused on the role of mothers (for exceptions, see Frome & Eccles, 1998;Pesu et al, 2016), to the relative neglect of the role of fathers' beliefs. However, it might be that mothers and fathers play a different role in their children's self-concept development (Frome & Eccles, 1998; MacGrath & Repetti, 2000;Maccoby, 1998).…”
mentioning
confidence: 99%
“…As the first hypothesis, we hypothesized that the associations of mothers' beliefs with adolescents' selfconcept of ability are stronger among girls than among boys whereas the associations of fathers' beliefs with adolescents' self-concept of ability are stronger among boys than among girls, as suggested by the socialization model (Maccoby, 1998). As the second hypothesis, we hypothesized that gender does not play a role in the connections between mothers'/fathers' beliefs and self-concept of ability because previous studies have not found these kinds of gender differences (Pesu at al., 2016;Simpkins et al, 2012).! Based one previous results by Pesu et al (2016), we also hypothesized that the role of mothers'/fathers' beliefs in self-concept of ability is stronger among high-than low-performing students.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Pesu et al (2016), the impact of teachers' beliefs on first-grade students' self-concept of…”
Section: Self-concept Of Abilitymentioning
confidence: 99%